Efek Gom MImba terhadap Kadar SCFA Digesta Sekum pada Tikus yang Diberi High Fat High Fructose Diet - Claudya Seline Diana Putri (Fakultas Kedokteran, 2026)
High Fat High Fructose Diet (HFFD) causes dysbiosis and decreased production of short-chain fatty acids (SCFAs). SCFAs are metabolites produced by gut microbiota during the fermentation of undigested carbohydrates. SCFA production occurs primarily in the cecum. These metabolites play a role in health by providing energy for colonocytes and maintaining the integrity of the intestinal barrier. Decreased SCFA levels due to HFFD cause epithelial damage and increased intestinal permeability. Prebiotic intake can improve dysbiosis and increase SCFA production. Neem gum (Azadirachta indica) from the neem tree contains undigested polysaccharides that have the potential to act as a prebiotic and increase SCFA production. This study aimed to evaluate the effect of neem gum on cecal digesta SCFA levels in rats fed HFFD. This study was a true experimental randomized post-test-only control group. Rats were divided into three groups: KN given aquadest (4% DMSO); K- given HFFD (4 ml/200 gbw); and P were given neem gum at a dose of 7.5 g/kgbw and HFFD (4 ml/200 gbw). This treatment was administered via oral gavage daily for 28 days. On day 29, the mice were terminated with ketamine-xylazine at doses of 80 mg/kg body weight and 5 mg/kg body weight intraperitoneally, followed by exsanguination. Cecal digesta were then collected for SCFA levels quantification. Data were analyzed using one-way ANOVA. The average cecal digesta SCFA levels in the KN group was 71.30 mM; K- was 48.39 mM; and P was 39.40 mM. One-way ANOVA showed no significant difference between groups (p>0.05). In conclusion, neem gum does not increase cecal digesta SCFA levels in rats fed HFFD.
The Effect of Neem Gum on Digesta Caecum SCFA Levels in Rats Fed a High Fat High Fructose Diet
Finalisasi Repo 23 Juni 2026_Yudi
Keywords: neem gum; SCFA; High Fat High Fructose Diet; Dysbiosis